PENGARUH UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI - Damayanti, Krisna; Dewi, Nurma Gupita (JAB (Jurnal Akuntansi & Bisnis), 2025)
This study aims to obtain empirical evidence regarding the effect of company size and leverage on profitability. This study uses 17 food and beverage companies listed on the IDX for the period 2021-2023. The data collection method uses documentation data. The data analysis technique uses multiple linear regression analysis. The results of this study indicate that company size has a significant positive effect on profitability, while leverage has a negative and significant effect on profitability in food and beverage companies listed on the IDX. This study contributes to investor decision making based on company value in food and beverage company entities. The implications of this study can provide benefits for investors and entities to find out prospects and provide additional information for readers and other researchers